Efektivitas REBT pada Regulasi Emosi Korban Pelecehan di Sekolah Kota Cirebon - Hanifiyyah Muthohharoh; Imelda Ayuningsih; Siti Nurhalisa; Mumtaz Afridah (Jurnal Riset Psikologi, 2026)
Abstract. Sexual harassment in school settings can impair adolescents' emotion regulation, as reflected in the tendency to suppress feelings of sadness while expressing excessive anger. This condition highlights the need for psychological interventions that enable victims to regulate their emotions more adaptively. This study aimed to examine the effectiveness of Rational Emotive Behavior Therapy (REBT) in improving emotion regulation among adolescent victims of sexual harassment at a school in Cirebon, Indonesia. The study was grounded in Gross's emotion regulation theory and Ellis's REBT approach, which emphasizes transforming irrational beliefs into more rational ones. A qualitative case study design was employed. The participant was selected using criterion-based case selection, namely an adolescent victim of sexual harassment who demonstrated maladaptive emotion regulation. Data were collected through in-depth interviews, observations during the counseling process, and documentation, and analyzed using data reduction, data display, and conclusion drawing. The intervention consisted of three sessions: initial assessment, REBT using the journaling technique, and evaluation. The findings indicate that REBT was effective in helping the participant develop more rational beliefs, improve anger regulation, and gradually accept and express sadness in a more adaptive manner. These findings contribute to the development of school counseling services by providing an alternative intervention to enhance emotion regulation and support the psychological recovery of adolescent victims of sexual harassment. Abstrak. Kasus pelecehan seksual di lingkungan sekolah dapat mengganggu regulasi emosi remaja, seperti kecenderungan menekan emosi sedih dan mengekspresikan kemarahan secara berlebihan. Kondisi ini menunjukkan perlunya intervensi psikologis yang membantu korban mengelola emosi secara lebih adaptif. Penelitian ini bertujuan mengkaji efektivitas Rational Emotive Behavior Therapy (REBT) dalam meningkatkan regulasi emosi pada remaja korban pelecehan di salah satu sekolah di Kota Cirebon. Kajian didasarkan pada teori regulasi emosi Gross dan pendekatan REBT Ellis yang menekankan perubahan keyakinan irasional menjadi rasional. Penelitian menggunakan pendekatan kualitatif dengan metode studi kasus. Subjek dipilih melalui criterion-based case selection, yaitu remaja korban pelecehan dengan regulasi emosi tidak adaptif. Data dikumpulkan melalui wawancara mendalam, observasi, dan dokumentasi, kemudian dianalisis menggunakan reduksi data, penyajian data, dan penarikan kesimpulan. Intervensi dilaksanakan dalam tiga pertemuan meliputi asesmen, REBT dengan teknik journaling, dan evaluasi. Hasil menunjukkan bahwa REBT cukup efektif membantu korban mengembangkan pola pikir yang lebih rasional, mengendalikan kemarahan, serta menerima dan mengekspresikan emosi sedih secara lebih adaptif. Temuan ini berkontribusi sebagai alternatif layanan bimbingan dan konseling sekolah untuk meningkatkan regulasi emosi serta mendukung pemulihan psikologis remaja korban pelecehan.